Digital Public History and Archives in Greece - Chrysanthopoulos, Christos (Journal of Integrated Information Management, 2024)
Purpose - In the current online context, the work of historians and archivists crosses multiple levels. Archival institutions, digital public history research projects, and broader activity in cultural heritage management have shaped many new archival digital repositories. The purpose of this article is to review this kind of online activity in Greece and highlight relevant concerns for managing historical archives online. Design/methodology/approach - This article presents digital archival repositories of archival institutions, cultural and information organisations and history research projects. It highlights the need for classification by the creator to improve the evaluation of the content and architecture of digital repositories. Findings - A core point from the review is the need for more collaboration between scientists, as new technologies, media, and the web have created fluid boundaries between disciplines Originality/value - A convergence between research and academic institutions and memory institutions and the development of joint scientific projects is in the interest of the preservation of historical archives but also of the community to which the stakeholders involved in such projects are addressed.